ENERGY AS A DEVELOPMENT PREREQUISITE FOR ECONOMIC AND SOCIETY - Soefjan Tsauri (Research Center for Chemistry - LIPI, 2000)
The concept of energy as a development prerequisite is discussedin view of its role in Indonesia; a large country endowed with richnatural energy resources, with a dominant rural population.Renewable energy resources and their utilization is reviewed.Lessons can be obtained from typical income-generating energyprojects which is relevance for the small and medium scaleenterprises. A study or model of ellergy use in Indonesia using amarket allocation approach is noted, in which its relationship withair pollution issues are analyzed. The allocation of energyresources in Indonesia has the characteristics of a multidimensionalproblem. This is difficult to be resolved satisfactorily, as we knowth at thcis is part of a wider picture of the national development.The strategy includes people-centered initiatives, in anticipationof the open, competitive market in this globalized era. This paperdiscusses also the implication of energy technology developmentto the Indonesian energy economics. Basic issues related to theresearch capability, the priorities, and the allocation of resources(or research and development in Indonesia are also reviewed.Keywords: Indonesia; renewable energy resources; incomegeneratingenergy projects; model of energy use; air pollution;energy technology development.